"I'm aging faster": social participation as experienced by individuals aging with a traumatic brain injury. (29th July 2022) - Turcotte, Samuel; Simard, Pascale; Piquer, Olivier; Lamontagne, Marie-Eve
ABSTRACT: Objectives: 1) To get an insight into the experience of aging with traumatic brain injury (TBI), and 2) explore intervention avenues perceived as promising for the social participation of this population. Method: Through an exploratory descriptive study, in-depth semi-structured interviews were conducted with aging TBI survivors recruited in a nonprofit community organization whose mission is to support the social participation of people living with TBI. Thematic analysis was done on qualitative data, using a hybrid approach of deductive and inductive analysis. Results: Ten aging TBI survivors with an average age of 64.9 years were interviewed. Participants expressed the perception of declining faster and with greater limitations than their fellow seniors unchallenged by TBI but also of having social participation opportunities due to their condition. A list of ten facilitators (e.g., doing activities in synch with life story) and five barriers (e.g., unequal levels of disability) to their social participation emerged. Conclusion: Social participation is crucial to TBI-affected individuals' healthy aging. Nonprofit community organizations should offer opportunities for participation, mobilize environmental resources, foster self-confidence, and support the achievement of meaningful personal projects to enable the social participation of people aging with TBI.